2004
DOI: 10.1182/blood-2004-02-0514
|View full text |Cite
|
Sign up to set email alerts
|

Mastermind critically regulates Notch-mediated lymphoid cell fate decisions

Abstract: IntroductionNotch signaling plays a central role in multiple developmental processes. During blood and lymphoid development, Notch proteins influence several hematopoietic lineages. At the T-cell/B-cell branchpoint, Notch promotes T-cell at the expense of B-cell differentiation. 1,2 More recent data implicate Notch1 in the early generation of the hematopoietic stem cell (HSC) pool during embryogenesis 3 and Notch2 in marginal zone B-cell (MZB) development. [4][5][6] Notch family members also have been postulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
230
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(242 citation statements)
references
References 34 publications
10
230
2
Order By: Relevance
“…Importantly, these effects are consistent with phenotypes caused by the inactivation of canonical Notch signaling in these compartments, because loss of the transcription factor CSL blocks both T-cell development and MZB cell generation Tanigaki et al, 2002). Not unexpectedly, then, the expression of DNMAML1 in bone marrow cells abrogated canonical Notch signaling, inhibiting both T-cell development and MZB cell generation (Maillard et al, 2004). Taken together, these data revealed that the MAML genes collectively are essential in mediating physiological Notch functions.…”
Section: Identification Of Maml Proteins and Investigations Into Theisupporting
confidence: 61%
“…Importantly, these effects are consistent with phenotypes caused by the inactivation of canonical Notch signaling in these compartments, because loss of the transcription factor CSL blocks both T-cell development and MZB cell generation Tanigaki et al, 2002). Not unexpectedly, then, the expression of DNMAML1 in bone marrow cells abrogated canonical Notch signaling, inhibiting both T-cell development and MZB cell generation (Maillard et al, 2004). Taken together, these data revealed that the MAML genes collectively are essential in mediating physiological Notch functions.…”
Section: Identification Of Maml Proteins and Investigations Into Theisupporting
confidence: 61%
“…4, G and H). Although DNMAM has been shown to be an effective inhibitor of signaling mediated by Notch2 in previous studies (35), these data may suggest that NICD2 is functioning independently of MAM in this specific cellular context. Certainly, additional studies are needed to validate this hypothesis; however, the molecular basis for the lack of NICD2 inhibition by DNMAM was not pursued further in this study.…”
Section: Generation Of Csl Mutantcontrasting
confidence: 41%
“…Mammalian MAML was shown to stabilize the RBP/NICD bound to DNA during activation of target genes [102]. In vivo, the importance of MAML has been impressively demonstrated with dominant-negative MAML, which completely blocks all Notch-mediated transcriptional activation [106]. This tool has been exploited to study the physiological role of "canonical" (RBP-J dependent) Notch signaling in detail, reviewed in [107].…”
Section: Coactivators Of Notchmentioning
confidence: 99%